Analisis Pengaruh Dominasi Pemasaran Tradisional Terhadap Kinerja Manajerial dan Keuangan pada UMKM Ketan Hitam Karamel Purwakarta: Penelitian - Ajeng Yustika; Evi Khopipah; Yosy Yuliantini; Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to examine how the dominance of traditional marketing affects managerial and financial performance of Ketan Hitam Karamel Purwakarta MSME. Data were collected through observation, interviews, and direct assistance involv-ing business legality, digital marketing, digital payment, branding, and basic finan-cial recording. The results show that reliance on conventional marketing limits mar-ket reach, reduces managerial efficiency, and hinders proper financial administra-tion. However, the MSME has strong potential for growth through digital promo-tion, QRIS adoption, and brand strengthening. The assistance provided supports improvements in legality, marketing capability, and financial organization. The study concludes that shifting toward modern and integrated marketing systems is essential to enhance overall business performance.